GENETIC VARIABILITY AND CHARACTER ASSOCIATION IN DIVERSE GENOTYPES OF BARLEY (HORDEUM VULGARE L.) - J. SINGH,; L. C. PRASAD,; A. H. MADAKEMOHEKAR,; S. S. BORNARE, (The Bioscan, 2014)
Genetic diversity is a primary prerequisite for improvement in genetic makeup of plant through breeding. So an experiment was conducted to investigate the genetic diversity among fourteen genotypes of Barley (Hordeum vulgare L.). The mean data estimated were subjected to analysis of variance, correlation coefficient and path analysis to identify promising genotypes for ten quantitative traits, during rabi 2011-12 and 2012-13. High GCV and PCV were observed for number of effective tillers per plant (29.86, 28.97), peduncle length (30.96, 30.67) and grain yield per plant (21.82, 20.72). The character association study revealed significant positive association of grain yield per plant with 1000 grain weight (rp=0.83), peduncle length (rp=0.51), number of effective tillers per plant (rp =0.46) and plant height (rp =0.18). Hence by exercising selection for these characters, it may be possible to isolate superior, high yielding genotypes. Path coefficient analysis revealed high positive direct effect of 1000 grain weight followed (0.72) by number of effective tillers per plant (0.62), number of grains per ear (0.41), and plant height (0.25).